Viral infections in cardiometabolic risk and disease between old acquaintances and new enemies - Cristina Vassalle (Exploration of Cardiology)
Atherosclerosis is a chronic disease, characterized by chronic inflammation, endothelial dysfunction, and lipid deposition in the vessel. Although many major, well-identified risk factors for atherosclerosis [e.g., hyperlipidemia, hypertension, type 2 diabetes (T2D), smoking habit, and obesity] explain a lot about the risk, there is a considerable number of patients who develop atherosclerotic damage and undergo adverse events without presenting any of these established modifiable risk factors. This observation has stimulated an urgent need to expand knowledge towards the identification of additional, less established risk factors that may help in the assessment of risk and fill the gap of knowledge in the cardiovascular (CV) setting. Among them, the hypothesis of a possible relationship between viral infectious agents and atherosclerosis has risen since the early 1900s. However, there is still a great deal of debate regarding the onset and progression of CV disease in relation to the roles of the pathogens (as active inducers or bystanders), host genomic counterparts, and environmental triggers, affecting both virus abundance and the composition of viral communities. Accordingly, the aim of this review is to discuss the current state of knowledge on infectious agents in the atherosclerotic process, with particular focus on two environmental-related viruses, as examples of familiar (influenza) and unfamiliar [severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)] disease triggers.